A system dynamics simulation of the Malaysian rice policy - Ramli, Nurul Nadia (2012)
Among the agricultural industries in Malaysia, the rice industry is the most highly protected, with a web of policy intervention in place to ensure the sustainability of the industry. There are three types of government intervention which are import restrictions, production subsidies and price supports. This study therefore attempts to simulate the impacts of government policy on the Malaysian rice industry in terms of its production, demand, trade and self-sufficiency level (SSL) with changes in policy instruments. A system dynamics model was employed in simulating the impacts of changes in the government policies. The simulation result indicated that the decrease in quantity of import quota leads to a decline in rice stock. Based on the simulation results, the rice stock showed an s shaped growth followed by a decline for the period of 2015. After that period, the rice stock will decline gradually per year. This scenario occurs due to the imposition of import quota that restricts the amount of rice that could be imported. Consequently, this leads to the decline in rice stock as the rice stock should be released in order to meet demand. The percentage of decline is about 17 per cent as compared to the baseline scenario. Simulation result indicated that the fertilizers used can give a significant impact to the yield. The removal of NPK fertilizer subsidy will lead to the decline in the yield obtained. The percentage decline in yield is about 24 percent. This occurs because the paddy farmers do not buy the additional NPK fertilizer, resulting in the decline in yield obtained. Thereafter, this leads to the decline in the SSL as the population continues to increase. Percentage decline in SSL is about 25.47 percent. A simulation on the price support revealed that it can give a positive impact to the farmers’ gross income. The result suggests that if the government removes the price support policy, the farmers’ gross income will decrease about 18.4 percent. This is because under this policy, farmers will earn additional income of about RM248.10 for each metric tonne of paddy they produce. In other words, for each metric tonne of paddy production, the farmers will gain RM248.10. Thus, withdrawal of the price support policy may result to the decrease in farmers’ gross income. The simulation results indicated that the introduction of new variety of paddy leads to increase in yield, and hence also increase in the production level. The percentage increase in yield and production is about 3 percent per year in 2015 and 2021. Nevertheless this may not be able to sustain the industry in terms of the targeted selfsufficiency level due to the increase in population. The simulation results also suggested that from 2011 until 2014, the decrease of percentage in SSL is about 2 percent per year. In 2015 until 2016 the percentage decrease in SSL declines to 0.5 percent due to the increase in rice production because of the introduction of new variety of paddy in year 2014 until 2016. Unfortunately after 2016, the percentage decline in SSL is back to its normal rate of about 2 percent per year until 2021. Again in 2021 if the new variety is being used, the percentage decline in SSL will be 0.5 percent per year. Therefore, it can be concluded that the overall policy implication indicated that paddy production in Malaysia cannot be sustained without fertilizer subsidy and price support programs. However due to trade liberalization, the initiatives to support the industry will be limited. The reduction in import quota leads to the decline in rice stock as the rice stock must be released to meet demand. Thus it is suggested that production must be increased to replenish the rice stock that has been released. Thus, the major policy implications from the study suggest that attention is be given to increase in the yield in order to meet demand. Therefore the government should introduce a policy that can encourage the farmers to increase their yield through acquisition of extra fertilizers or through better management practices. Special funds could be established to provide assistance for efficient paddy production and also to educate farmers to increase paddy production. Investments on research and development also should be encouraged since the introduction of new variety of paddy leads to the increase in the yield obtained. Investments by the government in the Research & Development, extension and technology transfer must continue and further strengthened. These efforts would considerably improve the agricultural productivity in order to ensure adequate supply of rice for the Malaysian population.